AUDIT – ASSESSMENT, INSPECTION OR CONTROL? - CONSTANŢA IACOB; FEEDA ABD ALMAJID SABBAR AL-ARAJI (Annals of the University of Petrosani: Economics)
The emergence audit concept has created a lot of confusion, on the one hand between its manifestations, on the other hand between it and the indigenous concepts that are more suggestive and at the same time more explicit. Both theory and practice show that the abolition of auditors within companies that have been subject to financial audit was the result of confusion created between the audit and statutory audit. On the other hand, long it was considered that if was set up internal audit do not need control, something which has to be seen from another perspective given that fact in reality internal control includes internal audit. These are the considerations which, in this article we try to sit concepts in their natural order and to emphasize the implications of corporate governance codes on the audit function.